Riwayat Kunjungan Antenatal Care dan Riwayat Kunjungan Posyandu sebagai Determinan Kejadian Stunting pada Balita di Wilayah Kerja Puskesmas Pekauman Kota Banjarmasin - Abdullah Abdullah; Norfai Norfai; Khairul Anam (HB PRESS, 2021)
Based on the results of Indonesian Basic Health Research in 2018, the prevalence of stunting decreases at the national level by 6,4% over a 5-year period, from 37.2% (2013) to 30.8% (2018). Meanwhile, there was an increase in children under five with normal nutritional status, from 48,6% (2013) to 57,8% (2018). Although there had been a decrease in stunting cases, the prevalence of stunting in Indonesia was still above 20%. According to WHO, the prevalence of stunted children was considered as public health significance if the prevalence was 20% or above. This research was an analytical survey using a case-control study design with a ratio of 1: 1. A total of 92 respondents were selected using purposive sampling technique. The data were analyzed using univariate and bivariate analyses. The bivariate analysis (chi-square test) was performed using a computer program with a confidence level of 95%. Based on the results of the study, there was no statistically significant relation of history of K4 antenatal care (ANC) visits and history of Posyandu visits to stunting incidence in children under five in the working area of Puskesmas Pekauman, Banjarmasin, in 2019. More in-depth research should be conducted to observe other variables that have high potential to have an association with stunting in children under five, such as parenting about the first 1,000 days of life and family income. These variables are most likely the fundamental variables related to the nutrient fulfillment of children under five and the perceptions of mothers who have children under five in providing care for their children.